An Analysis Racial Discrimination Depicted In This Is The Fire Novel - Octafia, Yani (Jurnal Pendidikan Bahasa dan Sastra, 2024)
The aim of this study is to analyze the issue of racial discrimination in the novel. The object of this research is the novel entitled This is The Fire (2021) by Don Lemon. This research uses a qualitative method by Creswell which presents analysis in dialogue and texts. In order to guide this research, the perspective of Fred L Pincus (1996) The types of racial discrimination. The analysis results in a clear that acts of racial discrimination against black people are experienced by anyone, anywhere, and in any field, from small children to adults, both in schools, shopping places, and the home environment, and also in the socio-economic and political fields. Racial acts of institutional discrimination type are the majority that cause deaths, namely carried out by white police against black people. Many incidents of discrimination have received justice because of the role of social media in showing the truth. Apart from that, acts of kindness such as upholding humanity and spreading love are the keys to overcoming acts of racial discrimination and creating peace